A novel frameshift mutation in SOX10 causes Waardenburg syndrome with peripheral demyelinating neuropathy, visual impairment and the absence of Hirschsprung disease. Issue 5 (9th March 2020) - Burke, Elizabeth A.; Reichard, Kyle E.; Wolfe, Lynne A.; Brooks, Brian P.; DiGiovanna, John J.; Hadley, Donald W.; Lehky, Tanya J.; Gropman, Andrea L.; Tifft, Cynthia J.; Gahl, William A.; Toro, Camilo; Adams, David
Abstract: Waardenburg syndrome (WS) is a group of genetic disorders associated with varying components of sensorineural hearing loss and abnormal pigmentation of the hair, skin, and eyes. There exist four different WS subtypes, each defined by the absence or presence of additional features. One of the genes associated with WS is SOX10, a key transcription factor for the development of neural crest‐derived lineages. Here we report a 12‐year‐old boy with a novel de novo SOX10 frameshift mutation and unique combination of clinical features including primary peripheral demyelinating neuropathy, hearing loss and visual impairment but absence of Hirschsprung disease and the typical pigmentary changes of hair or skin. This expands the spectrum of currently recognized phenotypes associated with WS and illustrates the phenotypic heterogeneity of SOX10 ‐associated WS.